2017
DOI: 10.1103/physrevlett.119.013601
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-Induced Strong Kerr Nonlinearity for Weak Quantum States of Light

Abstract: Strong nonlinearity at the single photon level represents a crucial enabling tool for optical quantum technologies. Here we report on experimental implementation of a strong Kerr nonlinearity by measurement-induced quantum operations on weak quantum states of light. Our scheme coherently combines two sequences of single photon addition and subtraction to induce a nonlinear phase shift at the single photon level. We probe the induced nonlinearity with weak coherent states and characterize the output non-Gaussia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…For instance, using sequences of photon addition and subtraction operations, it is possible to realize enabling tools for optical quantum technologies, such as noiseless linear amplification [ 12 ] and measurement‐induced strong Kerr nonlinearity at the single‐photon level. [ 13 ] Moreover, when the single‐photon addition process is coherently applied to a multimode field, delocalized heralded addition can entangle two or more field modes. [ 14 ]…”
Section: Discorrelation By Single‐photon Additionmentioning
confidence: 99%
“…For instance, using sequences of photon addition and subtraction operations, it is possible to realize enabling tools for optical quantum technologies, such as noiseless linear amplification [ 12 ] and measurement‐induced strong Kerr nonlinearity at the single‐photon level. [ 13 ] Moreover, when the single‐photon addition process is coherently applied to a multimode field, delocalized heralded addition can entangle two or more field modes. [ 14 ]…”
Section: Discorrelation By Single‐photon Additionmentioning
confidence: 99%
“…For the interaction of XKNLs, the magnitude of XKNL can obtain to , due to the electromagnetically induced transparency 67 , 68 . Recently, to the measurement-induced quantum operation on weak quantum states of light 69 can generate a strong XKNL at the single photon level for the applicable quantum information processing. Also, for the Hamiltonian, , of XKNL with , the scheme 70 have been designed in circuit QED where is coupling strength, is the transition strength between levels driven by a classical pump field with , detuning.…”
Section: Optical Procedures Via Xknls For Single Logical Qubit Informationmentioning
confidence: 99%
“…There have been several proposals to enhance the success rate of this gate at the expense of adding more resources 13,14 or vice-versa 15 . Costanzo et al 12 proposed an alternative implementation of a nonlinear sign gate that is shown in Figure 2. As illustrated in the upper part of the figure, the device produces a coherent superposition of photon subtractions that occur either before or after a photon addition.…”
Section: Nonlinear Sign Gatementioning
confidence: 99%